Komunitas Gulma Pada Pertanaman Pala (Myristica fragrans H) Belum Menghasilkan Dan Menghasilkan Di Desa Hutumuri Kota Ambon - W Palijama; Johan Riry; A.Y Wattimena (Faculty of Agriculture, Pattimura University, 2012)
Nutmeg (Myristica fragrans H) is native to Indonesia, which has been known as herbal plants. Its planting areas, however, are often hindered by the presence of unwanted plants. Weeds are among the plant pest organisms (PPO), which inhibit the growth, development and productivity of crops. Identification of dominant weed species is the first step in determining the success of weed control. This research was conducted in Hutumury Village, Ambon, with an aim to determine weed species composition and dominant weed species in producing and non producing (juvenile) nutmeg plantations. The process of data collection in the field was undertaken by a survey method. The results showed 18 weed species were found in the plantation of non producing phase and 13 weed species were found in the plantation of producing phase. In the producing plantation, the dominant weed species was Selaginella plana Heron with an SDR value of 57.80%. In the non producing plantation, the dominant weed was also Selaginella plana Heron with an SDR value of 44.42%. The overall dominant weeds in the nutmeg plantations belonged to the annual broad leaf weeds.